Axion-photon mixing and geometric phase. (June 2015) - Capolupo, A; Lambiase, G; Vitiello, G
Abstract: We report on recent results revealing the presence of a geometric phase in the axion- photon mixing. In laboratory observations its detection can reveal such mixing phenomenon and therefore prove the existence of axion like particles.